1996
DOI: 10.1046/j.1365-201x.1996.540305000.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle and heart antioxidant defences in response to sprint training

Abstract: Although endurance training enhances the antioxidant defence of different tissues, information on the effect of sprint training is scanty. We examined the effect of sprint training on rat skeletal muscle and heart antioxidant defences. Male Wistar rats, 16-17 weeks old, were sprint trained on a treadmill for 6 weeks. Total glutathione levels and activities of glutathione peroxidase, glutathione reductase, glutathione S-transferase and superoxide dismutase in heart and various skeletal muscles were compared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Variations in muscle cell activity related to aging (Pansarasa et al 1999), chronic immobilization (Kondo et al 1993), or exercise (Atalay et al 1996) modulate the activities of antioxidant enzymes such as cytosolic and mitochondrial superoxide dismutases, catalase, glutathione S -transferase, glutathione reductase, and glucose-6-phosphate dehydrogenase. Ethanol consumption has also been shown to induce CYP1A1/2 in rat skeletal muscle (Smith et al 2000), which supports the potential role of ethanol in the pathogenesis of alcohol-associated rhabdomyolysis in humans (Riggs 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in muscle cell activity related to aging (Pansarasa et al 1999), chronic immobilization (Kondo et al 1993), or exercise (Atalay et al 1996) modulate the activities of antioxidant enzymes such as cytosolic and mitochondrial superoxide dismutases, catalase, glutathione S -transferase, glutathione reductase, and glucose-6-phosphate dehydrogenase. Ethanol consumption has also been shown to induce CYP1A1/2 in rat skeletal muscle (Smith et al 2000), which supports the potential role of ethanol in the pathogenesis of alcohol-associated rhabdomyolysis in humans (Riggs 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified improved expression of antioxidants in hearts from exercised animals, including elevations in glutathione (44,133,161), glutathione redox cycle enzyme activities (8), catalase (202), and Mn-SOD (41,202). A number of studies (44,134,176) have also identified beneficial shifts in HSP expression, particularly HSP72.…”
Section: Restoration Of Conventional Protectionmentioning
confidence: 99%
“…Probably, the increase of the oxidative stress imposed to the body during periods of high work volume promotes transitory increase of the activity of antioxidant enzymes (17) . Within this context, Atalay et al (33) have observed in rats submitted to a six-week exercise protocol with supra-maximal intensity an increase in the muscular concentration of total GSH, GPx, glutathione-S transferase (GST) and GR. These results however, were obtained through a treadmill protocol with intensity equivalent to 200% of the VO 2máx of the animals, which makes the extrapolation difficult for humans.…”
Section: Lesões àS Fibras Muscularesmentioning
confidence: 99%